2013
DOI: 10.1016/j.oraloncology.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of temsirolimus and erlotinib in patients with recurrent and/or metastatic, platinum-refractory head and neck squamous cell carcinoma

Abstract: SUMMARY Objectives The epidermal growth factor receptor (EGFR) is a validated target in head and neck squamous cell carcinoma (HNSCC). In recurrent and/or metastatic (R/M) HNSCC, resistance to anti-EGFR therapy inevitably occurs. Downstream activation of the PI3K/Akt/mTOR pathway is an established resistance mechanism. Concurrent mTOR blockade may improve efficacy of anti-EGFR therapy. Materials and methods Erlotinib 150 mg daily and temsirolimus 15 mg weekly were administered to patients with platinum-refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 45 publications
2
66
0
1
Order By: Relevance
“…Dasatinib-related toxicities, including infection, pleural effusion, and edema, occurred at expected grades and frequencies. Notably, the edema was facial, a unique pattern that has been observed in patients with recurrent/metastatic HNSCC when exposed to mTOR inhibitors [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Dasatinib-related toxicities, including infection, pleural effusion, and edema, occurred at expected grades and frequencies. Notably, the edema was facial, a unique pattern that has been observed in patients with recurrent/metastatic HNSCC when exposed to mTOR inhibitors [28]. …”
Section: Resultsmentioning
confidence: 99%
“…In a Phase I study assessing a combination of temsirolimus, carboplatin, and paclitaxel in patients with SCCHN (NCT01016769), the confirmed objective partial response rate was 22% [68]. In a Phase II study in patients with recurrent or metastatic, platinum-refractory SCCHN, the combination of temsirolimus plus erlotinib was poorly tolerated [69], suggesting that investigation of more tolerable combinations of EGFR and PI3K/ AKT/mTOR pathway inhibitors in selected patients with SCCHN is warranted. Common toxicities associated with temsirolimus included fatigue, hyperglycemia, thrombocytopenia, diarrhea, peritonitis and pneumonia [68,69].…”
Section: Mtor Inhibitionmentioning
confidence: 99%
“…In a Phase II study in patients with recurrent or metastatic, platinum-refractory SCCHN, the combination of temsirolimus plus erlotinib was poorly tolerated [69], suggesting that investigation of more tolerable combinations of EGFR and PI3K/ AKT/mTOR pathway inhibitors in selected patients with SCCHN is warranted. Common toxicities associated with temsirolimus included fatigue, hyperglycemia, thrombocytopenia, diarrhea, peritonitis and pneumonia [68,69]. Temsirolimus is currently being tested in a Phase II study with or without cetuximab in patients with recurrent or metastatic head and neck cancer (NCT01256385) and in combination therapy with paclitaxel and carboplatin (NCT01016769).…”
Section: Mtor Inhibitionmentioning
confidence: 99%
“…A phase II study of this regimen in R/M-HNSCC is ongoing at the Memorial Sloan Kettering Cancer Center, while, in another phase II trial (TEMHEAD) reported at the ECC 2012 by Grünwald et al [97], temsirolimus reached its primary end point with a PFS at 12 weeks of 40%. However, a phase II trial of combination erlotinib-temsirolimus failed to achieve a satisfactory PFS (1.9 months), reporting a poor safety profile [98]. …”
Section: Recurrent or Metastatic Hnsccmentioning
confidence: 99%